Design of bridge interconnect converter for Micro-Power Park (MPP) - Lim, Ge Hao (Nanyang Technological University, 2020)
The bridge-interconnect converter (BIC) plays an important role in the integration and facilitation of the Micro-Power Pack (MPP) with the AC electrical utility grid. It should ensure that the quality and reliability of the transfer of electrical power between the systems is sufficiently acceptable and that it should also provide a seamless transition from having no connection to the grid (islanded) to having connection to the grid (grid-connected), complying with the IEEE-1547 grid-code requirements. This project report demonstrates the study of the various components and the design of a bridge-interconnect converter with two control modes, Grid-Forming and Grid-Tied, to be simulated using the MATLAB Simulink software and to also test for its reliability and effectiveness in satisfying the above-mentioned criteria. The design includes important components necessary to control the converter effectively. The Park’s transformation (dq0- transformation) and three-phase phase locked loop (3ph-PLL) is used to provide necessary information and controls about the grid voltage for the synchronization of the converter. Using the proportional-integral (PI) controller in the control loop gives the appropriate corrective response for a minimal steady state error to achieve a greater power quality, such as low harmonic distortions, within the system. Pulse signals are generated using the space-vector pulse-width modulation (SVPWM) technique that produces less harmonic distortion to control the switching pattern of the transistors in the converter. An LCL- (inductor-capacitor-inductor) filter with passive damping resistor is connected at the interface between the converter and the electrical utility grid to attenuate the higher order unwanted harmonic distortions.